COMPARISON OF DOUBLE-DISC SYNERGY, COMBINED DISC DIFFUSION, AND E TEST FOR METALLO-BETA-LACTAMASE DETECTION IN PSEUDOMONAS AERUGINOSA IN A TERTIARY CARE HOSPITAL - D, Varshini; A, Anu priya; J, LAITHAMBIGAI; P, Chitra Rajalakshmi; R, Saraswathi (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Pseudomonas aeruginosa is an important opportunistic pathogen associated with nosocomial infections. The metallo-beta-lactamases (MBLs) are an important class of carbapenemases which are predominantly produced by P. aeruginosa. This study is aimed to study the prevalence of MBLs among imipenem (IMP)-resistant P. aeruginosa and to evaluate three different methods of screening and detecting MBLs produced by P. aeruginosa. Methods: 100 isolates of P. aeruginosa were obtained from various clinical specimens, including pus, wound, sputum, urine, body fluids, and ET tips received at the laboratory from July 2021 to December 2021. Screening for MBL production among IMP-resistant P. aeruginosa was done by double-disc synergy test and combined disc test. Confirmation of MBL production was done by E-test. Results: Of the 100 P. aeruginosa isolates, 16 were IMP resistant, of which 16 are MBL producers. Most of the samples were obtained from 50 to 60 years followed by 40–50 and 60–70 were pus (50%) followed by sputum (20%), urine (15%), and body fluids (5%). Of the 100 isolates, 66 were isolated from females and 34 from males. Pus samples showed most MBL-producing isolates, accounting for 60.5%. MBL producers accounted for 90% of IMP-resistant cases using combined disc method and 100% using MBL E-strip test. By comparison, double-disc synergy test (DDST) retrieved 45% of Pseudomonas MBL producers. Conclusion: This study found moderate prevalence of Pseudomonas MBL producers (16/100). The study supports the use of combined disc-diffusion test and DDST for screening and confirming MBL producers of P. aeruginosa by E test where polymerase chain reaction is not available.